DIVERSITAS DAN METABOLISME MIKROBA SELAMA FERMENTASI KOMBUCHA: TINJAUAN LITERATUR - Hibatullah, Alnadia Yusriya; Primadiaty, Nurul Nisa (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Kombucha is a fermented beverage produced through the metabolic activities of a symbiotic culture of bacteria and yeast (SCOBY). It has attracted significant scientific and commercial interest due to its potential health-promoting properties, including its role in lowering cholesterol, blood pressure, and the risk of kidney damage, as well as improving immune system function. The growing demand for high-quality kombucha has highlighted the importance of understanding the microbiological aspects of its production. The fermentation process involves a complex interplay between acetic acid bacteria, various yeast species, and lactic acid bacteria, which contribute to the bioconversion of sucrose into ethanol, acetic acid, lactic acid, and other organic compounds. These metabolites are essential not only for the beverage’s sensory characteristics but also for its functional properties. Comprehensive knowledge of microbial diversity and their metabolic pathways is crucial for optimising fermentation conditions, enhancing product consistency, and minimising the risk of contamination. Moreover, the dynamic succession of microbial populations during fermentation affects the overall biochemical profile of the final product. This paper aims to review the dominant microorganisms involved in kombucha fermentation and analyse key biochemical changes during the fermentation process. Such insights are essential for process standardisation and the development of efficient, scalable production systems in the kombucha industry.